Emotional Intelligence and Creative Problem Solving in Business Leaders: A Structural Equation Modeling Approach - Anggun Wida Prawira; Azamat Nazarov; Javlonbek Khamraev (Journal of Loomingulisus ja Innovatsioon, 2025)
Emotional intelligence has increasingly been recognized as a critical factor influencing leadership effectiveness and the capacity for creative problem solving in complex business environments. This study aims to examine the relationship between emotional intelligence and creative problem-solving skills among business leaders by developing and testing a structural equation model. Data were collected from 362 senior managers across diverse industries through standardized instruments measuring emotional intelligence dimensions and creative problem-solving abilities. Structural Equation Modeling (SEM) was applied to analyze direct and indirect relationships between these constructs. The results revealed that emotional intelligence significantly and positively influences creative problem solving, with self-awareness and emotional regulation emerging as the strongest predictors. Indirect effects were also found, indicating that social awareness and relationship management enhance problem-solving outcomes through their influence on decision-making flexibility. The study concludes that leadership development programs emphasizing emotional intelligence can enhance creative capacities, supporting organizational adaptability and long-term competitiveness.